2013
DOI: 10.1158/1940-6207.capr-13-0178
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Metabolite, Apo-10′-Lycopenoic Acid, Inhibits Diethylnitrosamine-Initiated, High Fat Diet–Promoted Hepatic Inflammation and Tumorigenesis in Mice

Abstract: Obesity is associated with increased risk in hepatocellular carcinoma (HCC) development and mortality. An important disease control strategy is the prevention of obesity-related hepatic inflammation and tumorigenesis by dietary means. Here, we report that apo-10′-lycopenoic acid (APO10LA), a cleavage metabolite of lycopene at its 9′,10′-double bond by carotene-9′,10′-oxygenase, functions as an effective chemopreventative agent against hepatic tumorigenesis and inflammation. APO10LA treatment on human liver THL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
96
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 55 publications
9
96
1
Order By: Relevance
“…All changes obtained in rats after 4 weeks of being fed with HFD are reported in results, and have been repeatedly found in previous studies, [16][17][18][19][20][21][22]25 and allowed us to properly assay the therapeutic efficacy of ND plus LYC against ND alone.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…All changes obtained in rats after 4 weeks of being fed with HFD are reported in results, and have been repeatedly found in previous studies, [16][17][18][19][20][21][22]25 and allowed us to properly assay the therapeutic efficacy of ND plus LYC against ND alone.…”
Section: Discussionsupporting
confidence: 71%
“…[9][10][11][12] Potential health benefits of lycopene (LYC) have been studied for more than 75 years. 7,13,14 In particular, experimental studies have shown that LYC supplementation effectively prevents the development of various liver injuries 15 : Animals were fed during several weeks with a high-fat diet (HFD) and supplemented with LYC, [16][17][18] an LYC metabolite, 16,19,20 or tomato juice as a source of LYC, 21,22 to prevent diet-mediated steatosis, 16,18,22 diethylnitrosamine-initiated HFD-promoted hepatocarcinoma, 17,19,20 and a metabolic pattern from an HFD. 21 The aim of this study was to assess the ability of LYC to return liver steatosis and to revert hepatic morphological changes produced by an HFD.…”
Section: Introductionmentioning
confidence: 99%
“…This mono acid derivative (10 0 -apo-lycopenoic acid) was found to have other biologic activities such as suppression of lung tumorigenesis associated with modulation of cell cycle proteins such as p21and p27 [67]. Recently, the inhibitory effect of 10 0 -apo-lycopenoic acid on high fat dietpromoted hepatic inflammation and tumorigenesis was reported by Ip et al [68] who observed an elevation of the level of the sirtuin deacetylase sirt1 associated with reduced acetylation of target proteins including the NFkB active subunit p65; a reduction in the total level of p65 was noted. These results suggest that different lycopene metabolites (e.g., acids versus aldehydes) could inhibit the NFkB pathway by different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that these metabolites may exhibit more important biological roles than lycopene itself (9,14,15), and BCO2 ablation in mice altered lycopene metabolism (16,17). In particular, APO10LA supplementation was effective in inhibiting hepatic steatosis in genetically induced obese (ob/ob) mice (15) and attenuating high saturated fat diet (HSFD)-induced liver inflammation as well as tumor number and volume in C57Bl/6J mice (18). An important question remains as to whether the biological activity of lycopene could be different from its metabolite APO10LA in the absence of BCO2 expression.…”
Section: Introductionmentioning
confidence: 99%